An Analysis of Supply Chain Strategy and Integration Effects on Operational Performance of Micro, Small and Medium Enterprises (MSMEs) in Yogyakarta - shaumy, naila nourouz; nursyamsiah, siti (Jurnal Bisnis dan Manajemen, 2024)
This study explored the impact of supply chain strategy and supply chain integration on the operational performance of SMEs in Yogyakarta. The research aims to analyze the influence of supply chain strategy and integration on operational performance as well as investigate the mediating role of supply chain integration in the relationship between supply chain strategy and operational performance. The study employs a quantitative approach, utilizing a survey methodology with a sample of 100 SMEs in Yogyakarta. Data analysis is conducted using Structural Equation Modeling (SEM) via SmartPLS v.3. The findings found that supply chain strategy has a significant positive effect on supply chain integration among Yogyakarta's SMEs. Furthermore, supply chain integration demonstrates a significant positive influence on the operational performance of these SMEs. Notably, the results indicate that supply chain integration positively mediates the relationship between supply chain strategy and operational performance, highlighting its crucial role in enhancing organizational outcomes.